115k views
1 vote
Which choice is equivalent to the expression-2(-x+ 5y) + 3(2x - 6y)

1 Answer

2 votes

Answer:

No choice is given but the expression is simplified below:

Explanation:

Given that:

= -2(-x+ 5y) + 3(2x - 6y)

By Multiplying the constants into the brackets:

"-" sign before the bracket will alter inner signs

= 2x - 10y + 6x - 18y

Now add the same terms:

= (2x + 6x) - (10y + 18y)

= 10x - 28y

Now by taking 2 common:

= 2 (5x - 14)

i hope it will help you!

User Halofourteen
by
5.1k points